Crystallurical profile in sheep after ammonium chloride supplementation - Navarro, F. C. [UNESP]; Bentin, L. T. [UNESP]; Bovino, F. [UNESP]; Peiró, J. R. [UNESP]; Feitosa, F. L.F. [UNESP]; Mendes, L. C.N. [UNESP] (FapUNIFESP (SciELO), 2022)
Although urinary crystals are habitual components, urolithiasis formation is always preceded by these concretions. We aimed to identify the change in the crystalline profile in sheep supplemented with ammonium chloride. Twenty-five male sheep aged three months, feedlot and randomly distributed into three groups were used: Control Group (CG) n = 5 did not receive Ammonium Chloride; G200 Group (n=10) (200mg/kg) of Ammonium Chloride for 56 consecutive days; G500 Group (n=10) (500mg/kg) of Ammonium Chloride for 56 consecutive days, administered daily orally. Sampling times and clinical evaluation were performed at seven days, with M0 (immediately before Ammonium Chloride), M1 (seven days after) until M8, totaling 70 days of feedlot. Urine samples were performed to identify the presence, type, and quantity of crystals. There was an increase in crystalluria in all groups in relation to time due to dietary influence, mainly in the CG, which presented more crystals of amorphous calcium phosphate and calcium oxalate. In addition, the G500 Group presented a higher presence of urate/uric acid crystals after urinary acidification, which are closely related to urinary pH.
Perfil cristalúrico em ovinos suplementados com cloreto de amônio
Keywords: Crystals; Urinalysis; Urinary acidification; Urine; Urolithiasis